A novel method for the characterization of through-thickness shear constitutive behavior of composites. (1st March 2023) - Hao, Ziqing; Ke, Hongjun; Li, Na; Wang, Xiaoyu; Li, Jinming; Liu, Liu
Abstract: This work presents a novel experimental method to characterize the through-thickness shear response for fiber-reinforced polymer composite materials. A sandwich short-beam shear specimen with a thin 0° laminated face sheet bonded with a thick 90° laminated core is proposed. A combination of a finite element model-based stress calculation and a full-field surface strain measurement in a custom sandwich specimen under bending is used in the method. An entire interlaminar shear response in the 2–3 principal material plane has been generated using a regression of FEM-calculated shear stress and DIC-measured shear strain. The measured 23-plane interlaminar shear stress–strain response was very close to the 23-plane Iosipescu test and the plate-twist shear test, but a higher ultimate shear strain was achieved. Transverse tensile failure with a 45° fracture angle originated from the transverse shear stress on the neutral surface. A full set of the three-dimensional stress–strain constitutive relations has been assessed using one short-beam-shear test method, and identical nonlinear shear stress–strain responses with distinct ultimate shear strengths have been observed in the three principal material planes for the generic FRP tape material in this work for the first time. Graphical abstract: Highlights: A sandwich short-beam-shear test method is proposed to obtain the shear behavior. The entire shear responses of composites were measured in the 2-3 plane. The shear stress-strain behaviors obtained from three test methods were compared. The full set of 3D constitutive relations is evaluated using a single test method.